Headway teacher's book : (Oxford University Press, 1993)
Headway is for students who want to use English accurately and fluently, and to communicate with ease in both social and everyday situatiuons. This latest addition to the Headway family offers the beginner and false beginner all the best features of the Headway package plus the newer features of `Everyday English' sections, an integrated vocabulary syllabus, and revision and self-access sections after every four units.